Dimeric Oxidovanadium(IV) Complex Bearing 1,10-Phenanthroline - Charamzová, Iva; Honzíček, Jan; Kalenda, Petr; Vinklárek, Jaromír; Císařová, Ivana (My University, 2020)
New crystals of di-mu-methoxido-bis[(2-ethylhexanoato-kappa O)oxido(1,10-phenanthroline-kappa N-2,N')vanadium(IV)], C42H52N4O8V2, have been synthesized, characterized by elemental analysis, infrared spectroscopy, electron paramagnetic resonance and X-ray diffraction analysis. The compound crystallizes in the monoclinic space group P2(1)/c: a = 13.0656(11) angstrom, b = 9.1474(8) angstrom, c = 17.0299(14) angstrom, beta = 94.387(4)degrees, Z = 2, R-gt = 0.0617, wR(F-2) = 0.169, T = 150(2) K. The dimeric oxidovanadium(IV) complex consists of two [(VO)-O-IV(OCOC7H15)(phen)] units connected with two methanolate bridges. The vanadium atoms have a distorted octahedral environment with four oxygen and two nitrogen atoms. The V=O bond length is 1.601(3) angstrom; the V-O bond lengths in the symmetrical V2O2 core are 1.973(2) and 2.007(3) angstrom. The vanadium-oxygen bond lengths in the carboxylate are 1.974(3) angstrom. The V-N interatomic distances depend on the configuration towards the oxidoligand. Preliminary experiments on solvent-borne alkyd resins revealed promising catalytic activity in the auto-oxidation process.
Dimerní oxovanadičitý komplex s 1,10-fenantrolinem
Keywords: crystal structure; krystalová struktura